Systematic Reviews and Meta-Analyses - ISICAM, ISICAM; BA, Mahdi; Y, Purnamasari; JK, Fajar; Pranata, Raymond; Yonas, Emir (The Indonesian Heart Association, 2018)
Systematic Reviews and Meta-Analyses; Abstracts of the 10th Indonesian Society of Interventional Cardiology Annual Meeting Jakarta, 23-25 November 2018